The Hygienic Estimation of Influence of Training Sessions Using Electronic Tablet on Functional State of Students - V. R. Kuchma; M. I. Stepanova; Z. I. Sazanyuk; M. A. Polenova; I. E. Aleksandrova; N. O. Berezina; A. Yu. Makarova (Сеченовский вестник, 2015)
The use of modern electronic gadgets leads to high rates of work, better assimilation of knowledge and a high level of preparedness of students. Introduction in educational process of new e-learning-notebooks, tablets, e-readers require justifi cation of their safety for health of pupils, and the rapid modernization of electronic gadgets, the speed of these studies. The widespread use of information technology has potential negative consequences associated with Freestyle or unwitting violation or disregard of user’s safe modes that must be followed in the application. The purpose of the research was to study the infl uence of Tablet PC e-learning in secondary school on the functional state of the students. The study was conducted at the beginning and end of lessons using electronic tablets, and without them the 235 pupils of 7–8 classes. Analysis of the responses of the functional systems of the grade 7 students at diff erent school organization not only not improved the tiring eff ects of lessons on using electronic tablets, but also showed greater resistance to fatigue from them than the traditional classroom because of hygienic management of lessons in applying e-learning: the optimal change of activity, the density of 60–80% of the lessons, the total duration of the work with the Tablet for the lesson-no more than 15 minutes continuous / no more than 4 minutes. Training using electronic textbook for eighth graders proved more arduous than classes without Tablet PC: by the end of the lesson, have dropped the speed and accuracy of work, IHI mental performance declined in 3 times, 51% of students complete lessons with explicit and visible fatigue. The infl uence of electronic tablet on tedious functional state of class 8 students due to a variety of reasons (high intensity training with frequent change of training), features of adaptation of pupils not only to new technical means of teaching, but also to the new subject, technical diffi culties in the development of e-learning tools. For an objective judgement on the impact of electronic textbooks on the functional State of an organism students need longer (minimum school year) monitoring.